(untitled) (Revista Contexto & Saúde, 2025)
Objective: The aim of this study was to report the effectiveness of the proposed tele-rehabilitation program to promote the respiratory rehabilitation and the functional recovery of people with post-COVID-19 syndrome. Method: 99 patients with COVID-19 sequelae participated in the tele-rehabilitation program, were shared in three groups: oxygen group (OG), COPD group (COPD-G), and general group (GG). The program lasted 12 sessions and included a protocol of respiratory exercises and muscle strengthening. Medical Research Council (MRC) and CR-10 Borg Scale were used to asses the patients at the beginning and at the end of the program, the oxygen saturation (SO2) and the heart rate (HR) were measured daily. Result: The patients had an increase of 5% in COPD-G (p<0.001) and 6% in OG/GG (p<0.001) for the SO2. For the MRC scale, patients had an increase of at least one point in COPD-G (p<0.001) and two points in OG/GG (p<0.001). The BORG scale values had a decrease of at least 5 and 4 points in the scale in COPD-G (p=0.003) and OG/GG (p<0.001) wich indicates that the intervention benefited the both groups. There were no significant differences between the initial and the final assessments for HR. Conclusion: The tele-rehabilitation program helped the pulmonary rehabilitation and the functional recovery of people with post-COVID-19 syndrome, and it also improved the muscular strengthen, the effort perception to do the exercises and the oxygen saturation. This program arose as a feasible, accessible and low cost assistance alternative that could be used beyond the pandemic period.